Dynamic Relationship of Guru and Shishya in the Sphere of Music: Exploring the bond between Guru and Shishya in the field of music (Journal of Advances and Scholarly Researches in Allied Education, 2013)
A study of dynamic relationship of Guru and shishya is considered very significant in music. One of the most pure and deeply inspirational relationships is that of a devoted teacher and a willing student.The ability to forge a positive, powerful relationship between a student and teacher may seem like a difficult task first but can be easily accomplished by creating a strong learning environment. The learning is not a one way process alone; an effective learning environment is where all individuals involved learn from each other. While students learn a particular subject from a teacher, the teacher learns how to improve her teaching skills and make the lessons more interesting by gaining insights from the students. Thus, both parties learn from each other. The relationship of learner and mentor in the sphere of music education is considered very important in music the bond between mentor and learner is following from the ancient tradition of music. As for as the research article is concern the researcher in this research work has written about the relationship of Guru Shishya in the field of music.